Evaluation of clinical comorbidities in cognitively impaired patients with depressive symptoms - Funari,Rossana Maria Russo (2007)
Abstract In demented patients, depressive symptoms as well as cognition and clinical comorbidities can interact and induce a complex condition of severity and handicap. Objective: The objective of this study was to evaluate the influence of depressive symptoms in cognitively impaired patients on associated clinical comorbidities in geriatric patients. Methods: One-hundred-thirty-eight (138) patients were divided into two groups: the first contained cognitively impaired patients with depressive symptoms while the second comprised cognitively impaired patients without depressive symptoms. To quantify comorbidities, the Modified CIRS Scale was used. Results: Out of the 138 patients, 52 were cognitively impaired with depressive symptoms and 86 were cognitively impaired without depressive symptoms, both having mean CDR of 1.74 (moderate dementia). The patients with depressive symptoms used more drugs (4.98 per patient vs. 3.45 per patient without depressive symptoms; p=0.001), presented more comorbidities (3.24 per patient vs. 2.46 per patient without depressive symptoms; p=0.009). However, these comorbidities were neither more severe nor more complex in the patients with depressive symptoms, with mean Comorbidity Severity Index of 1.45 in patients with and 1.37 in patients without depressive symptoms (p= 0.078) and mean Comorbidity Complexity Index of 2.41 in patients with depressive symptoms and 2.01 in those without depressive symptoms (p=0.103). Conclusion: Cognitively impaired patients with depressive symptoms had a greater absolute number of comorbidities and took more drugs although these comorbid diseases were less severe and complex than in non-depressive cognitively impaired patients.